Tissue-specific effects of benzo[a]pyrene and DDT on microRNA expression profile in female rats - D. S. Ushakov; T. S. Kalinina; A. S. Dorozhkova; V. Y. Ovchinnikov; L. F. Gulyaeva (Вавиловский журнал генетики и селекции)
Many xenobiotics in the human environment, such as benzo[a]pyrene (B(a)P) and dichlorodiphenyltrichloroethane (DDT), may act as non-genotoxic carcinogens through epigenetic mechanisms, including changes in microRNA expression profile. In part, such disorders can be mediated by the activation of nuclear receptors, resulting in the activation of protein coding gene expression and microRNAs involved in malignant transformation of cells. Therefore, the aim of this study was to investigate the chain of events “xenobiotic administration – receptor activation – up-regulating microRNA expression – down-regulation target genes expression” as one of the key factors in the chemically-induced carcinogenesis. Using in silico methods, an analysis of the rat genome was carried out to find microRNAs putatively regulated by AhR (aryl hydrocarbon receptor) and CAR (constitutive androstane receptor), activated by BP and DDT, respectively. In particular, miR-3577 and -193b were selected as potentially regulated CAR, miR-207 was selected as a candidate for miR under AhR regulation. The results of the study showed that the treatment of female rats with DDT and B(a)P caused a tissue-specific changes in the expression of microRNAs and host genes in both acute and chronic administration of xenobiotics. To confirm the effects of xenobiotics on the microRNA expression, we also estimated the mRNA level of PTPN6, EIF3F, Cbx7, and Dicer1 genes potentially targeting miR-193b, -207, and -3577. The study has shown a high correlation between the expression of target genes and microRNAs; however these changes depended on the tissue types, the dose and time after xenobiotic treatment.